Walisongo’s Educational Leadership through Modelling and Fulfilment of Human Basic Needs - Susanto, Nanang Hasan (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
This study aims to trace the Walisongo’s (the Nine Saints) leadership model that is often considered successful in Islamizing the Javanese community in a relatively short time and almost without conflict. Through the literature search using analytic descriptive, this study brings the conclusion that based on the conventional leadership model division, the Walisongo’s leadership can be categorized into transformational leadership with characteristics capable of fostering trust, pride, loyalty, and respect of Javanese society. In addition, the Walisongo's leadership also conforms to the characteristics proposed by Tobroni, which include spiritual leadership, with characteristics based on the divine aspect, done with honesty and sincerely, drawing public sympathy and mobilizing them to follow the Walisongo’s teachings. This research also produces a finding that the success of Walisongo in educating the people of Java is due to their concern on the efforts to meet the basic needs of the society and provide models to follow.